2022
DOI: 10.3856/vol50-issue5-fulltext-2937
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Rhodoturula glutinis as a modulator of innate immune and oxidative stress-related genes in Oreochromis niloticus cultured in a Biofloc system

Abstract: The effect of live yeast Rhodoturula glutinis was evaluated on juvenile Oreochromis niloticus cultivated in a Biofloc system. Growth performance and the expression of innate response and relevant oxidative stress genes were evaluated after a 12-week feeding trial. Three experimental treatments were evaluated in a conventional tilapia culture (control), Biofloc culture (BFT), and Biofloc with the addition of the live yeast R. glutinis 1×106 CFU g-1 (BFT+Rg), with four replicates per treatment. In all cases, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Higher crude protein in the C/N20 treatment could be due to the richness of microorganism in the treatment [56], but diferences in nutritional compositions among diferent treatments might be due to diference in microbial community [81]. In the present study, the crude lipid and ash content were in the range as observed by Becerril-Cortés et al [57] in rice bran-developed biofoc except for lower crude protein. Lipid is the important source of metabolic energy for growth of fsh.…”
Section: Proximate Composition Of Biofocsupporting
confidence: 66%
See 1 more Smart Citation
“…Higher crude protein in the C/N20 treatment could be due to the richness of microorganism in the treatment [56], but diferences in nutritional compositions among diferent treatments might be due to diference in microbial community [81]. In the present study, the crude lipid and ash content were in the range as observed by Becerril-Cortés et al [57] in rice bran-developed biofoc except for lower crude protein. Lipid is the important source of metabolic energy for growth of fsh.…”
Section: Proximate Composition Of Biofocsupporting
confidence: 66%
“…Te presence of more nitrifying bacteria converts ammonia to nitrite and then nitrite to nitrate which might have resulted in increased nitrate-N concentration at a higher stocking density in BFT [28,56]. Becerril-Cortés et al [57] recorded similar nitrate-N concentration for tilapia fry. Te C/N ratio and stocking density have a signifcant efect on the TSS and foc volume.…”
Section: Discussionmentioning
confidence: 98%